Glial expression of Swiss cheese (SWS), the Drosophila orthologue of neuropathy target esterase (NTE), is required for neuronal ensheathment and function. - Dutta, S.; Rieche, F.; Eckl, N.; Duch, C.; Kretzschmar, D. (Disease models & mechanisms, 2016)
Mutations in Drosophila Swiss cheese (SWS) or its vertebrate orthologue neuropathy target esterase (NTE), respectively, cause progressive neuronal degeneration in Drosophila and mice and a complex syndrome in humans that includes mental retardation, spastic paraplegia and blindness. SWS and NTE are widely expressed in neurons but can also be found in glia; however, their function in glia has, until now, remained unknown. We have used a knockdown approach to specifically address SWS function in glia and to probe for resulting neuronal dysfunctions. This revealed that loss of SWS in pseudocartridge glia causes the formation of multi-layered glial whorls in the lamina cortex, the first optic neuropil. This phenotype was rescued by the expression of SWS or NTE, suggesting that the glial function is conserved in the vertebrate protein. SWS was also found to be required for the glial wrapping of neurons by ensheathing glia, and its loss in glia caused axonal damage. We also detected severe locomotion deficits in glial sws-knockdown flies, which occurred as early as 2?days after eclosion and increased further with age. Utilizing the giant fibre system to test for underlying functional neuronal defects showed that the response latency to a stimulus was unchanged in knockdown flies compared to controls, but the reliability with which the neurons responded to increasing frequencies was reduced. This shows that the loss of SWS in glia impairs neuronal function, strongly suggesting that the loss of glial SWS plays an important role in the phenotypes observed in the sws mutant. It is therefore likely that changes in glia also contribute to the pathology observed in humans that carry mutations in NTE.